2022
DOI: 10.3389/fendo.2022.888948
|View full text |Cite
|
Sign up to set email alerts
|

Serum miRNA Profile in Diabetic Patients With Ischemic Heart Disease as a Promising Non-Invasive Biomarker

Abstract: The increasing morbidity and mortality of type 2 diabetic mellitus (T2DM) patients with ischemic heart disease (IHD) highlight an urgent need to identify early biomarkers, which would help to predict individual risk of development of IHD. Here, we postulate that circulating serum-derived micro RNAs (miRNAs) may serve as potential biomarkers for early IHD diagnosis and support the identification of diabetic individuals with a predisposition to undergo IHD. We obtained serum samples from T2DM patients either wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Similarly, it has been demonstrated that miR-615 is expressed in adipose tissue in humans and that its expression changes with the obesity ( 66 ). Moreover, the expression of this miRNA has also been identified in patients with diabetes ( 67 ). Together with miRNAs, our analysis also revealed changes in the expression of long non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been demonstrated that miR-615 is expressed in adipose tissue in humans and that its expression changes with the obesity ( 66 ). Moreover, the expression of this miRNA has also been identified in patients with diabetes ( 67 ). Together with miRNAs, our analysis also revealed changes in the expression of long non-coding RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that empagliflozin significantly improves cognitive impairment in frail older diabetics with HFpEF (Mone et al, 2022c), showing also a correlation between physical and cognitive impairment (Mone et al, 2022a). MicroRNAs (miRs) are small non-coding RNAs molecules of 18-24 nucleotides, which typically repress messenger RNAs (mRNAs) by binding their 3′ untranslated region (Santulli, 2015;Fridrichova and Zmetakova, 2019;Stavast and Erkeland, 2019;Hu et al, 2021;Mirzaei et al, 2021;Mone et al, 2021b;Bielska et al, 2022;Karagiannopoulos et al, 2022;Mauro et al, 2022;Moisoiu et al, 2022;Qiu et al, 2022;Traber and Yu, 2022;Yaylim et al, 2022;Zeng et al, 2022). Substantial evidence has shown that miRs exert their activity in many biological processes and several miRs have been proposed as biomarkers and potential targets of novel therapeutic strategies (Creemers et al, 2012;Wronska et al, 2015;Barwari et al, 2016;Zarone et al, 2017;Chen et al, 2018;Wong et al, 2018;Morelli et al, 2019;Kawasaki et al, 2020;Wang et al, 2020;Fonseca et al, 2021;Gambardella et al, 2021;Bonnet et al, 2022;Gambardella et al, 2022a;Gambardella et al, 2022b;Kansakar et al, 2022;Varzideh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%